The Holiness of God in the Old Testament - Obloy, Leonard (Journal of Dharma, 1983)
"Be holy, for 1, the Lord, your God, am holy." This command found in Leviticus is in many ways a summary of the religious experience of the Israelites. It speaks of an understanding of God, Yahweh as "holy", and suggests the possibility of human relationships with God. Moreover, such relationships are explained as participations in the very holiness of God Himself. Quite naturally then, holiness is a key, pivotal concept or the religion of the Old Testament. Indeed, holiness is as vast, wide, and deep as the mystery of Yahweh Himself. Gradually this Hebrew understanding of holiness deepened and developed as the Israelites listened, reflected, and responded to God’s call.